Differences in the fungal communities nursed by two genetic groups of the alpine cushion plant, Silene acaulis. Issue 23 (21st November 2018) - Roy, Julien; Bonneville, Jean‐Marc; Saccone, Patrick; Ibanez, Sébastian; Albert, Cécile H.; Boleda, Marti; Gueguen, Maya; Ohlmann, Marc; Rioux, Delphine; Clément, Jean‐Christophe; Lavergne, Sébastien; Geremia, Roberto A.
Abstract: Foundation plants shape the composition of local biotic communities and abiotic environments, but the impact of a plant's intraspecific variations on these processes is poorly understood. We examined these links in the alpine cushion moss campion ( Silene acaulis ) on two neighboring mountain ranges in the French Alps. Genotyping of cushion plants revealed two genetic clusters matching known subspecies. The exscapa subspecies was found on both limestone and granite, while the longiscapa one was only found on limestone. Even on similar limestone bedrock, cushion soils from the two S. acaulis subspecies deeply differed in their impact on soil abiotic conditions. They further strikingly differed from each other and from the surrounding bare soils in fungal community composition. Plant genotype variations accounted for a large part of the fungal composition variability in cushion soils, even when considering geography or soil chemistry, and particularly for the dominant molecular operational taxonomic units (MOTUs). Both saprophytic and biotrophic fungal taxa were related to the MOTUs recurrently associated with a single plant genetic cluster. Moreover, the putative phytopathogens were abundant, and within the same genus ( Cladosporium ) or species ( Pyrenopeziza brassicae ), MOTUs showing specificity for each plant subspecies were found. Our study highlights the combined influences of bedrock and plant genotype on fungal recruitment into cushion soils and suggests the coexistence of two mechanisms, an indirect selection resulting from the colonization of an engineered soil by free‐living saprobes and a direct selection resulting from direct plant–fungi interactions. Abstract : We report four main findings. First, the two local S. acaulis subspecies exhibit differential soil abiotic engineering. Second, fungal communities beneath cushions of the two plant subspecies are largely different, thus related to genotype variability. Third, the differences are in part be explained by a differential soil abiotic engineering. Finally, this divergence is most pronounced for fungal species that tightly interact with plants including putative phytopathogenic fungi.